FINITE ELEMENT ANALYSIS OF STRESS DISTRIBUTION ON HIGH-HEELED SHOES - Sivarao S.; Sivakumar S.; Ramesh S.; Lee K.Y.S.; Salleh M.S.; Ali M.A.M.; Rao D.; Kumaran K.; Pujari S.; Vatesh U.K. (Taylor's University, 2023)
The use of high-heeled shoes has become an increasingly popular among women. However, this type of footwear has contributed a lot to several foot related problems such as muscle pain, spasms, and lower back pain. During static standing position, excess pressure is seen to be located at heel and forefoot region. Finite Element Analysis (FEA) can offer an alternative means to solve biomechanics problems. Preliminary investigations have been done to find out relevant information regarding the design of high-heeled shoe and computational model approach to simulate static standing condition. Static simulation is carried out to study the correlation between heel heights, shoe material, and stress distribution. Peak stress was seen located at the heel region and is in good agreement to previous findings. The current study offers a prior computational approach, which is capable to predict and estimate comprehensive data and results which aims to aid researchers in determining best parameters for design of high-heeled shoes. School of Engineering, Taylors University.